2019
DOI: 10.31861/biosystems2019.02.243
|View full text |Cite
|
Sign up to set email alerts
|

Pedogeochemical barriers of heavy metals’migration distribution in chernozems soil profile at Kryvorizhzhya

Abstract: The basic regularities of the distribution of heavy metals’migration pedogeochemical barriers in soil profile of the chernozems ordinary and southern at Kryvy Rih mining and metallurgical regions were analyzed. It was pointed out that heavy metals’migration pedogeochemical barriers is a part of the soil horizon or soil profile, where there is a significant concentration of individual chemical elements as a consequence of the substitution-reaction phenomenon. Pedogeochemical barriers are classified into five ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The result of the investigation clearly indicated that in Haplic Chernozems the maximum organic matter and carbonate content takes place in the ABk horizon (Sposito 2008). In our opinion, these substances determine the maximum of Fe, Mn and Zn concentrations in this soil horizon (Savosko 2019a(Savosko , 2019b.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The result of the investigation clearly indicated that in Haplic Chernozems the maximum organic matter and carbonate content takes place in the ABk horizon (Sposito 2008). In our opinion, these substances determine the maximum of Fe, Mn and Zn concentrations in this soil horizon (Savosko 2019a(Savosko , 2019b.…”
Section: Discussionmentioning
confidence: 73%
“…That is why, the natural soil profile can be considered as a combination of pedogeochemical barriers to elemental migration. As we know it, these barriers are a part of the soil profile, where significant accumulation of several chemical elements occurs (Savosko 2019a(Savosko , 2019b.…”
Section: Discussionmentioning
confidence: 99%